Analysis seric minerals in lactation sows of two commercial farms. (FAVE Sección Ciencias Veterinarias, 2021)
Mineral nutrition is essential for profitable production. Health affected is not provided proper levels minerals. Objective of the present work was to analyze mineral profile in serum of sows in lactation, province Santa Fe (A), Entre Rios (B) and fed with diets minerals of inorganic origin. Blood serum samples 68 sows, Farm A (in field) and Farm B (in stabled form) were analyzed. Mineral concentrations were determined by means of atomic absorption spectrophotometry; ANOVA was applied to these data. Mean values and their standard deviations obtained are: Calcium (Ca) (mg/dL): 8,61±3,44/ 8,11± 1,73; Phosphorus (P) (mg/dL): 2,66a±0,90/ 3,53b± 1,16; Magnesium (Mg) (mg/dL): 2,25a±0,30/ 1,89b±0,35; Sodium (Na) (mEq/L): 160,98a±15,47/ 138,53b±9,48; Potassium (K) (mEq/L): 3,42±0,24/ 3,58±0,33; Iron (Fe) (µg/dL): 62,74a±6,07/ 94,82b±19,19; Copper (Cu) (ppm): 1,63a±0,35/ 1,01b±0,32; Zinc (Zn) (ppm): 1,82a±0,5/ 1,50b±0,42, for farms A and B respectively. Na and Zn averages were observed slightly above upper limit of normal range. Copper in farm B was observed below normal range. Significant difference (“a” and “b” P
Keywords: sow, serology, minerals, lactation